Association of cognitive domains with postural instability/gait disturbance in Parkinson's disease. Issue 7 (July 2015) - Kelly, V.E.; Johnson, C.O.; McGough, E.L.; Shumway-Cook, A.; Horak, F.B.; Chung, K.A.; Espay, A.J.; Revilla, F.J.; Devoto, J.; Wood-Siverio, C.; Factor, S.A.; Cholerton, B.; et al.
Abstract Introduction Research suggests an association between global cognition and postural instability/gait disturbance (PIGD) in Parkinson disease (PD), but the relationship between specific cognitive domains and PIGD symptoms is not clear. This study examined the association of cognition (global and specific cognitive domains) with PIGD symptoms in a large, well-characterized sample of individuals with PD. Methods Cognitive function was measured with a detailed neuropsychological assessment, including global cognition, executive function, memory, visuospatial function, and language. PIGD symptoms were measured using the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) Part III, Motor Examination subscale. Multiple linear regression analyses were performed to assess the relationship between cognition and PIGD symptoms with models adjusting for age, sex, education, enrollment site, disease duration, and motor symptom severity. Results The analysis included 783 participants, with mean (standard deviation) age of 67.3 (9.7) years and median (interquartile range) MDS-UPDRS Motor Subscale score of 26 (17, 35). Deficits in global cognition, executive function, memory, and phonemic fluency were associated with more severe PIGD symptoms. Deficits in executive function were associated with impairments in gait, freezing, and postural stability, while visuospatial impairments were associated only with more severe freezing, and poorer memory function was associated only with greater postural instability. Discussion While impairments in global cognition and aspects of executive functioning were associated with more severe PIGD symptoms, specific cognitive domains were differentially related to distinct PIGD components, suggesting the presence of multiple neural pathways contributing to associations between cognition and PIGD symptoms in persons with PD.